Covid 19 Pandemic: Contribution of family well-being on the children's academic performance / Norlaila Abdullah Chik and Nor'jila Mohamad - Abdullah Chik, Norlaila; Mohamad, Nor'jila (2021)
A strategy of research and development in family wellbeing has developed through the National Family Policy (NFP). Family wellbeing is essential for a developed society (Noor et al., 2014). Families that can make the right and wise decisions, such as managing the family's basic needs and dealing with family problems in an increasingly stressful society, need to be nurtured to live a happier and healthier life. However, the family's wellbeing was slightly affected when the world was shocked by the Covid 19 pandemic at the end of 2019, which started in Wuhan, China. Covid 19 pandemic has spread in China and worldwide through various means such as tourism, education, employment, etc. Malaysia also confront the Covid 19 pandemic when the first case of death of a priest in Sarawak occurred until the government had to take security measures by declaring a Movement Control Order (MCO) from 18 March 2020 to 31 March 2020 initially, but the situation worsened as the number of cases increased until now.